Rent-Seekers, Profits, Wages and Inequality The Top 20% - Mihályi, Péter; Szelényi, Iván (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
"This is an original account of two of the most important social trends today: rising income inequality and declining class mobility. Underlining the contemporary relevance of classical economics and sociology, the authors show how rent-seeking has created a new elite that threatens democracy and entrenches an upper middle class, where economic advantage is passed from one generation to the next. This is social science in the grand tradition - sweeping and urgent in its analysis and implications." - Bruce Western, Professor of Sociology, Columbia University, USA "The most important book on recent trends in socio-economic inequality since Piketty`s Capital in the 20th Century." -- Karl Ulrich Mayer, Stanley B. Resor Professor Emeritus of Sociology and Professor, Institution for Social and Policy Studies, Yale University, USA; Director Emeritus, Max Planck Institute of Human Development, Germany "Inequality is one of the biggest challenges of our time. This book provides an important addition to the debate, combining in an original way economic, sociological and historical analysis" - Gerard Roland, E. Morris Cox Professor of Economics and Professor of Political Science, University of California, Berkeley, USA Mihályi and Szelényi provide a timely contribution to contemporary debates about inequality of incomes and wealth, offering a careful examination of various sources of rent in contemporary societies, and considering several policy options to reduce inequality in order to preserve the meritocratic nature of liberal democracies. While Rent Seekers, Profits, Wages and Rents acknowledges the rapid and disturbing increase of incomes and wealth in the top 1 or 0.1%, it focuses on the increasing rent component of incomes and wealth in the top 20% as even more consequential. The attention to cutting-edge issues on inequality in macroeconomics, political science and sociology will appeal to social scientists interested in income distribution and wealth accumulation.